REGULATION OF THE FINANCIAL ACTIVITIES OF ENTERPRISES IN THE CONDITIONS OF THE WAR ECONOMY, CURRENT STATE AND FORECASTS (World of finance, 2023)
Introduction. Enterprises conduct their financial activities to ensure a stable financial condition, efficient management, and the achievement of planned goals and results. A strong and stable economy of the state contributes to their development and business activity. Today, it is difficult for enterprises to conduct their usual financial and economic activities, because the fullscale military aggression of russia caused them huge losses and forced them to adapt to new business conditions in a short period of time.The purpose of the article is to clarify the essence of the financial activity of economic entities and the peculiarities of its implementation in the conditions of martial law, an overview of regulatory measures aimed at stabilizing the financial and economic activity of enterprises that are implemented by the state during the period of full-scale war, as well as substantiating the need for their further use and efficiency.Methods. Analysis, synthesis, comparison, generalization, graphic method were used in the research process.Results. The theoretical foundations of the essence of financial activity have been studied and the author’s interpretation has been proposed. The current economic situation in the state and its influence on the financial activity of economic entities have been analyzed. Forecasts of domestic and international institutions regarding the expected level of key economic indicators have been considered. The need for implementation of regulatory actions of the state to support the activities of enterprises has been argued.Conclusions. Ukrainian enterprises continue to operate despite the large-scale challenges of the extensive war, keeping the economy in working condition, providing revenues to the budget to support the country’s defence and security. The state coordinates and regulates their activities, develops and implements new, flexible, dynamic and effective tools and tries to ensure the most favurable conditions for stable functioning and conducting financial and economic activities.